Knowledge transfer of climate-ecosystem-interactions between science and society - Introducing the Climate Whirl concept - Juurola, Eija; Korhonen, Janne F. J.; Kulmala, Liisa; Kolari, Pasi; Taipale, Ulla; Rasinmaki, Jussi; Ruuskanen, Taina; Haapoja, Terike; Back, Jaana; Levula, Janne; Riuttanen, Laura; Kyro, Ella-Maria; et al. (Finnish Environment Institute, 2016)
Peer reviewed